2004
DOI: 10.1074/jbc.m409207200
|View full text |Cite
|
Sign up to set email alerts
|

(S)-2,3-Di-O-geranylgeranylglyceryl Phosphate Synthase from the Thermoacidophilic Archaeon Sulfolobus solfataricus

Abstract: The core structure of membrane lipids of archaea have some unique properties that permit archaea to be distinguished from the others, i.e. bacteria and eukaryotes. (S)-2,3-Di-O-geranylgeranylglyceryl phosphate synthase, which catalyzes the transfer of a geranylgeranyl group from geranylgeranyl diphosphate to (S)-3-O-geranylgeranylglyceryl phosphate, is involved in the biosynthesis of archaeal membrane lipids. Enzymes of the UbiA prenyltransferase family are known to catalyze the transfer of a prenyl group to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 28 publications
(18 reference statements)
1
32
0
Order By: Relevance
“…A back and forth swinging motion of ␣3* could also act like a molecular ratchet. In this way, the AfGGGPS TIM-barrel modification might promote the delivery of its hydrophobic product in proximity to the membrane bilayer, where the next enzyme in the pathway lies in wait (13).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A back and forth swinging motion of ␣3* could also act like a molecular ratchet. In this way, the AfGGGPS TIM-barrel modification might promote the delivery of its hydrophobic product in proximity to the membrane bilayer, where the next enzyme in the pathway lies in wait (13).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, a magnesium counterion will support the pyrophosphate leaving group. Asp 13 , an absolutely conserved residue in all GGGPS proteins ( Fig. 2A), is well positioned to act as a ligand for a Mg 2ϩ ion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second ether bond is formed by the membrane protein DGGGP synthase that belongs to the UbiA prenyltransferase family. DGGGP synthase of Sulfolobus solfataricus was expressed in E. coli, and the enzymatic activity of the purified protein was found to be specific for the substrates GGPP and GGGP (Hemmi et al, 2004) synthesizing the product 2,3-di-O-geranylgeranylglyceryl phosphate (DGGGP). In a later study, DGGGP synthase was shown to accept both the S and R form of GGGP, thus being rather enantio unselective (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%